Simultaneous trapping of 85Rb & 87Rb in a far off resonant trap - Gorges, Anthony R., author; Roberts, Jacob Lyman, advisor; Leisure, Robert Glenn, 1938-, committee member; Eykholt, Richard Eric, 1956-, committee member; Marconi, Mario C., committee member (Colorado State University. Libraries, 2010)
The experiments described in this thesis were focused on the physics of simultaneous trapping of 85Rb and 87Rb into a Far Off Resonant Trap (FORT), with a view towards the implementation of a non-evaporative cooling scheme. Atoms were first trapped in a Magneto Optical Trap (MOT) and from there loaded into the FORT. We investigated the effects of loading the FORT from a MOT vs. an optical molasses; observing that the molasses significantly improved the trapped atom number. The ultimate number of atoms trapped is determined by a balance between efficient laser cooling into the FORT and light-assisted collisional losses from the FORT. We have studied and measured the loss rates associated with light-assisted collisions for our FORT, measuring both heteronuclear and homonuclear collisions. It was discovered that induced long range dipole-dipole interactions between 85Rb and 87Rb have a significant impact on FORT loading. This interaction interferes with the loading into the trap and thus limits the number of atoms which can be trapped in the FORT under simultaneous load conditions. Despite this limitation, all required experimental parameters for our future measurements have been met. In addition to these FORT studies, we have found a technique which can successfully mitigate the effects of reabsorption in optically thick clouds, which is a limitation to the ultimate temperature an atom cloud will reach during light-based cooling. Planned future measurements for this project include the creation of a variable aspect ratio FORT; along with investigating collision assisted Zeeman cooling.
Department Head: Hans D. Hochheimer.
Keywords: ultracold collisions; ultracold optical trap; Atoms -- Cooling; Laser cooling; Low temperature research; Nuclear physics